2021
DOI: 10.1029/2021ja029243
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Jupiter's X‐Ray Auroral Hot Spot Emissions Using Chandra

Abstract: To help understand and determine the driver of jovian auroral X‐rays, we present the first statistical study to focus on the morphology and dynamics of the jovian northern hot spot (NHS) using Chandra data. The catalog we explore dates from December 18, 2000 up to and including September 8, 2019. Using a numerical criterion, we characterize the typical and extreme behavior of the concentrated NHS emissions across the catalog. The mean power of the NHS is found to be 1.91 GW with a maximum brightness of 2.02 Ra… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(28 citation statements)
references
References 77 publications
(189 reference statements)
1
27
0
Order By: Relevance
“…The X‐ray emission along the bright boundary of the swirl region (e.g., Johnson et al., 2017 ; Stallard et al., 2016 ) also either shifted or vanished. One proposed source of X‐ray emissions is that they are produced by processes along the magnetopause (e.g., reconnection, Kelvin Helmholtz instabilities, and/or Chapman‐Ferraro currents) (Bunce et al., 2004 , Dunn et al., 2016 , 2017 ; Kimura et al., 2016 ; Weigt et al., 2020 , 2021 ). A shifting of the swirl boundary may fit with a theoretical interpretation that involves a shifting of the ionospheric mapping of the magnetopause to lower latitudes caused by a solar wind compression.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The X‐ray emission along the bright boundary of the swirl region (e.g., Johnson et al., 2017 ; Stallard et al., 2016 ) also either shifted or vanished. One proposed source of X‐ray emissions is that they are produced by processes along the magnetopause (e.g., reconnection, Kelvin Helmholtz instabilities, and/or Chapman‐Ferraro currents) (Bunce et al., 2004 , Dunn et al., 2016 , 2017 ; Kimura et al., 2016 ; Weigt et al., 2020 , 2021 ). A shifting of the swirl boundary may fit with a theoretical interpretation that involves a shifting of the ionospheric mapping of the magnetopause to lower latitudes caused by a solar wind compression.…”
Section: Discussionmentioning
confidence: 99%
“…We note that we only simulated emission from inside Region X since we are seeking to test whether, when the spatial uncertainties of the instrument are accounted for, emission from this region can explain the observed X‐rays in the DPR. In the main text, we chose to use the UV brightness as our probability map because X‐ray emissions are highly variable from observation to observation (e.g., Dunn et al., 2016 ; Dunn, Gray, et al., 2020 ; Jackman et al., 2018 ; Weigt et al., 2021 ). In Supporting Information S1 , we show results from simulating the X‐ray source regions using a uniform probability across Region X and note that the error bars on the mean from the uniformly distributed X‐ray photons overlap those from the UV‐distributed X‐ray photons.…”
Section: Numerical Tests Of Source Locations For Dpr Photonsmentioning
confidence: 99%
“…We use the same 29 observations which were explored in a statistical study by Weigt, Jackman, et al. ( 2021 ) of the northern auroral emissions. Like that study, one observation is omitted (ObsID 18303) due to Jupiter’s position on the chip of the detector being shifted away from the aim point.…”
Section: Data Sets and Methodsmentioning
confidence: 99%
“…This interpretation is based on data taken from the Chandra X‐ray Observatory (CXO) (Weisskopf et al., 2000 ) and the X‐ray Multi‐Mirror Mission (XMM‐Newton) (Jansen et al., 2001 ), fitted with the EUV97 solar proxy model (Tobiska & Eparvier, 1998 ), that suggest the vast majority (∼90%) of disk X‐ray emissions are produced from solar X‐rays elastically scattered from Jupiter’s upper atmosphere, with ∼10% fluorescent production of carbon K‐shell X‐rays from methane (Cravens et al., 2006 ; Maurellis et al., 2000 ). Previous case studies have reported instances where the disk X‐rays show similar day‐to‐day variability as the solar X‐rays (Bhardwaj et al., 2005 ), with no evidence of the quasi‐periodic flaring occasionally seen in the auroral X‐rays (e.g., Gladstone et al., 2002 ; Jackman et al., 2018 ; Weigt, Jackman, et al., 2021 ).…”
Section: Introductionmentioning
confidence: 97%
“…A comprehensive study of all Chandra observations of Jupiter from 1999 to 2015 revealed that, when present, the periods of the pulsations in the northern and southern auroral X-rays range from ∼8-45 min, and that these pulsations can vary on the timescale of a Jupiter rotation (∼10 hr, Jackman et al, 2018). A more recent study by Weigt et al (2021) echoed these results when expanding the catalog to 2019 (∼2.3-36 min) to the concentrated X-ray auroral emissions. They also found these periodicities in the brightest emissions to be spatially dependent when applying a strict location criterion.…”
mentioning
confidence: 99%